1992
DOI: 10.1080/00140139208967393
|View full text |Cite
|
Sign up to set email alerts
|

Development of microcomputer-based mental acuity tests

Abstract: Recent disasters have focused attention on performance problems due to the use of alcohol and controlled substances in the workplace. Environmental stressors such as thermal extremes, mixed gases, noise, motion, and vibration also have adverse effects on human performance and operator efficiency. However, the lack of a standardized, sensitive, human performance assessment battery has probably delayed the systematic study of the deleterious effects of various toxic chemicals and drugs at home and in the workpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In a previous article (Turnage et al 1992), we stated that mental tests can provide an indication of the onset, duration, and severity of impairment in operational performance which may aid ergonomic research. We observed that, although the advent of microcomputers expands the potential for such' assessment over paper-and-pencil media by permitting more rapid, diverse, and accurate assessment of capabilities, suitability requirements for such test materials are needed to satisfy metric criteria and practical factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous article (Turnage et al 1992), we stated that mental tests can provide an indication of the onset, duration, and severity of impairment in operational performance which may aid ergonomic research. We observed that, although the advent of microcomputers expands the potential for such' assessment over paper-and-pencil media by permitting more rapid, diverse, and accurate assessment of capabilities, suitability requirements for such test materials are needed to satisfy metric criteria and practical factors.…”
Section: Discussionmentioning
confidence: 99%
“…Under sponsorship from the US National Aeronautics and Space Administration and later the US National Science Foundation, a series of experiments was conducted to evaluate the tests' mechanized psychometric properties, their sensitivities, and their correlations with other computer tests and with tests of intelligence. These findings are reviewed in Turnage et al (1992).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…There are now scores of computer-based performance assessment tools available commercially (Psychological Corp., 1996); researchers continue to develop tests that can be obtained at little or no cost (e.g., Elsmore, 1994;McKnight & MeKnight, 1994). The development, characteristics, and desired properties of such tools have been discussed in the literature (e.g., Turnage, Kennedy, Smith, Baltzley, & Lane, 1992). Test characteristics such as measurement stability, task definition, reliability, and performance stabilization time are critical factors influencing the acceptability and utility of such tests, particularly for repeated administration of the tests over time.…”
mentioning
confidence: 99%